(3cJGH aj GdbUUs
(3ChdgG (B:s
(3bjd Mci Efg cGf ai bOje GdReGf edc ef edhc GdYQH hcGf eScfg ai eOjfI YXjeI hgj HCWQGa aGQS JSei fje QhR s
(3BNQgG (B:s
(3BNQ GdehLhO efg bGd dgG Ef OYGc Gdedc hSGdc bhdi dg Cf gPG GdZdGe fXQfi jhekG hadb bdHg Hi hcJH Edi jSFdfi GdehOI hVef di eGdkG cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs